Modern Muslim identities : negotiating religion and ethnicity in Malaysia - Hoffstaedter, Gerhard (Copenhagen : NIAS Press, 2011)
This title explores the relationship between the Malaysian state and its citizens in creating and maintaining fixed identities. The book focuses on new modalities of being Muslim in a modern world.
Identity formation and its articulation -- Malayness and Islam -- Ordered spaces: naming places and defining boundaries -- Engineering Muslim Malay identities -- Other Malays and Malaysia(n)s: resistance and change -- Islamicity: experiencing the devine light -- Between a cosmopolitan ethic and the politicide of the Malays -- Conclusion
Includes bibliographical references (pages 233-261) and index.
Print version record.
Master record variable field(s) change: 072
Keywords: Muslims -- Malaysia; Islam -- Malaysia; SOCIAL SCIENCE -- Discrimination & Race Relations; SOCIAL SCIENCE -- Minority Studies; Islam; Muslims; Malaysia; Electronic books